Tracer study investigation into reactor mixing characterisation - Enbaia, Ali Elsaeh (Trinity College (Dublin, Ireland). Department of Civil, Structural and Environmental Engineering, 2005)
The hydraulic characterization of flow through a reactor is essential for a complete understanding of the process for which the reactor has been designed. The goal of hydraulic characterization of a continuous flow process is to track the behaviour of different portions of the fluid flow through the reactor. Most real systems have complicated hydraulic characteristics where reactors have poor inlet/outlet configurations, dead zones, internal circulations, and short circulating and/or bypassing of the fluid flow. The technique which is used to quantify the hydraulic charactenstics of the fluid flow through the reactor can be divided into two main sequences.
Keywords: Civil Structural and Environmental Engineering, Ph.D.; Ph.D. Trinity College Dublin